The Impact of Social Media on Hotel Management: Branding, Engagement, and Reputation in Lagos State, Nigeria - Hembafan Pius Ogoina; Henry Amaegberi; Shammah Obianuju Jonathan; Aziba-anyam Gift Raimi (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2026)
Rationale: The pervasive influence of social media on consumer behavior and marketing strategies necessitates a comprehensive understanding of its impact on the hospitality industry. As hotels increasingly leverage digital platforms for engagement and reputation management, examining the effectiveness of various social media strategies and their implications becomes crucial for optimizing marketing efforts and enhancing brand identity. Objective: This study aims to investigate the impact of social media on hotel management, branding, engagement, and reputation in the hospitality sector. Method: A mixed-methods approach was employed, involving quantitative surveys of hotel customers and qualitative interviews with hotel marketing managers. Data on demographic characteristics, social media usage patterns, primary purposes of social media usage, perceptions of hotel branding, and reputation management practices were collected and analyzed to identify trends and insights. Results: The data reveals that promotional offers and discounts (100%), user reviews (90%), and visual content (80%) are critical factors influencing consumer hotel choices. Collaboration with influencers, user-generated content, live video content, and social media advertising all demonstrated 100% effectiveness in engaging audiences and building brand identity. Pre-social media, 40% of hotels promptly addressed issues, while post-social media, this decreased to 20%, with private resolutions increasing from 20% to 30%. Conclusions: Social media significantly influences consumer behavior in hotel selection and booking decisions. The shift in reputation management practices underscores the need for hotels to balance transparency with effective conflict resolution strategies. Social media strategies that leverage influencers, user-generated content, and dynamic visual content are crucial for enhancing engagement and brand identity. Recommendations: Hotels should prioritize influencer collaborations, encourage user-generated content, and invest in high-quality visual media. Implementing regular updates, engaging contests, and targeted promotional offers can drive bookings and enhance customer satisfaction. Proactive reputation management and transparent communication are essential for maintaining a positive public image. Significance Statement: This study provides valuable insights into the transformative impact of social media on the hospitality industry, offering evidence-based strategies and policy recommendations for optimizing digital marketing efforts. The findings underscore the importance of a strategic and multifaceted approach to social media, highlighting its role in shaping consumer behavior, enhancing brand identity, and driving business growth.